Linking agri‐environment scheme habitat area, predation and the abundance of chick invertebrate prey to the nesting success of a declining farmland bird. Issue 2 (23rd June 2022) - McHugh, Niamh M.; White, Patrick J. C.; Moreby, Steve; Szczur, John; Stoate, Chris; Leather, Simon R.; Holland, John M.
Abstract: 1. Across Europe, farmland bird populations have continued to decline since the 1970s owing to the intensification of farming practices. Studies of such declines have tended to focus specifically on either the impacts of habitats (nesting and foraging), nest predators or prey availability on bird demographics. The study presented here provides new insights into the relative effects of each of these factors on yellowhammer nest survival. The yellowhammer was selected for this study as it is a UK Red‐Listed bird species whose population is in decline across much of Europe. 2. We use a long‐term dataset of 147 nests, monitored between 1995 and 2007, to provide an insight into how yellowhammer nest survival is influenced by nesting habitat (nest concealment and nest height), foraging habitats (habitat coverage within 100 m of nests), the removal of nest predators (magpie Pica abundance as an inverse measure of avian predator removal through gamekeeping) and food availability (measured with a D‐vac invertebrate suction sampler). 3. Our results indicated that yellowhammer hatching success was negatively related to the coverage of spring agri‐environment scheme habitats, a group which represents invertebrate‐rich agri‐environment habitats, but hatching success increased with nest height. Fledging success was positively related to the coverage of the seed‐rich habitat wild bird seed mixture. The farm‐level abundance of yellowhammer chick‐food invertebrates declined over the study period. 4. Our results highlight the importance of simultaneously considering multiple agents that shape avian breeding success, that is their ability to produce offspring, to inform conservation management. Our key finding for land managers relates to the positive relationship between the proportion of seed rich foraging habitat within the yellowhammer's average foraging range and yellowhammer fledging success, which shows that a habitat intended primarily to provide winter food resources is also important to breeding birds. Chick food abundance in this habitat was, however, similar to broadleaf and cereal crops. We recommend that this habitat should be provided near to potential yellowhammer nesting sites and adjacent to invertebrate‐rich agri‐environment scheme habitats such as beetle banks and conservation headlands to further boost invertebrate resources for a declining farmland bird. Abstract : Our results highlight the importance of simultaneously considering multiple agents that shape avian breeding success, that is. their ability to produce offspring, to inform conservation management. For land managers, our key finding relates to the positive relationship between the proportion seed rich foraging habitat within the yellowhammers average foraging range and yellowhammer fledging success, which shows that a habitat intended primarily to provide winter food resources is also important to breeding birds. Chick food abundance in this habitat was similar to crops. We therefore recommend that this habitat be provided near potential yellowhammer nesting sites and invertebrate‐rich agri‐environment scheme habitats such as beetle banks and conservation headlands are positioned adjacent to further boost invertebrate resources for a declining farmland bird.